FRACTURING LIQUID DESIGN AND ECONOMIC ANALYSIS FOR LOW PERMEABILITY AND HIGH TEMPERATURE - Saputra, Novan Ade (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
Mirabelle 01 M01 well is a developed-stage well which has undergone drilling since February 2020 until May 3th 2020. It has 13000 ft depth and dominated with sandstone layers and some shaly inserts. This well is a high temperature (300 F), low permeability (0.5-5 mD) and porosity well which casues hydraulic fracturing should be done in this well. Aim: to carry out fluid fracturing design analysis by considering additional materials and economics. The perforation in this well divided into 2 perforations, first perforation has been 297 ft long and located at 12143 ft-12440 ft of well depth. The second perforation has been 45 ft in length and is located at 12,730 ft-12,685 ft of well depth. Payzone of this well is dominated by sandstone which is determined from the low gamma ray data. This Mirabelle 01 M01 well has high resistivity due to the resistivity log. Water mix used for the formation is a neutral water mix but still has several negative ions with corrosive properties such as SO42- and Cl-. Acid inhibitors are needed to remove these ions and prevent corrosive to be happened. Scale inhibitors are also needed to be added to prevent scale formation caused by Mg2+ ions which are contained in the mix water. From the average pressure calculation, the closure pressure was found about 7914.67 psi. The young modulus found from 8-10 Mpsi which indicates that the formation has high stiffness. The base of the fracturing fluid used is low price water-base fluid with guar gum polymer which can produce hydroxypropilguar (HPG) that don't ruin the formation even if the formation is in the high temperature. Borate ions are used to be crosslinker agents that binds metal ions with polymers. To split polymers molecules, sodium salt from the peroxydisulphate is used to be the gel breaker.